2020
DOI: 10.3390/nano10101920
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Growth Morphologies of Ga2O3 Nanowires on Different Substrates

Abstract: Gallium oxide (Ga2O3) is a new wide bandgap semiconductor with remarkable properties that offers strong potential for applications in power electronics, optoelectronics, and devices for extreme conditions. In this work, we explore the morphology of Ga2O3 nanostructures on different substrates and temperatures. We used silver catalysts to enhance the growth of Ga2O3 nanowires on substrates such as p-Si substrate doped with boron, 250 nm SiO2 on n-Si, 250 nm Si3N4 on p-Si, quartz, and n-Si substrates by using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…However, the "β" phase Ga 2 O 3 has had much attention as an excellent material for gas sensors [5], power devices [6], catalysis [7], and transparent conducting materials [8] due to its availability of single-crystalline substrates, high thermal and chemical stability, lower power loss, high electric breakdown field strength, controllability of conductivity, and high transparency in the visible region [9,10]. In addition, recently, Alhalaili et al (2020) studied the morphological characteristics of β-Ga 2 O 3 nanowires grown on different substrates with different temperatures and reported the suitable conditions to grow high-density unform β-Ga 2 O 3 nanowires on Si substrates [11]. The p-type doping is still a significant obstacle to the device application.…”
Section: Introductionmentioning
confidence: 99%
“…However, the "β" phase Ga 2 O 3 has had much attention as an excellent material for gas sensors [5], power devices [6], catalysis [7], and transparent conducting materials [8] due to its availability of single-crystalline substrates, high thermal and chemical stability, lower power loss, high electric breakdown field strength, controllability of conductivity, and high transparency in the visible region [9,10]. In addition, recently, Alhalaili et al (2020) studied the morphological characteristics of β-Ga 2 O 3 nanowires grown on different substrates with different temperatures and reported the suitable conditions to grow high-density unform β-Ga 2 O 3 nanowires on Si substrates [11]. The p-type doping is still a significant obstacle to the device application.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that high nitrogen (N 2 ) pressure (1-2 GPa) and high temperature (1400-1500 • C) is necessary to drive the reaction between Ga and N 2 to form GaN [49], which was not achieved in our experiments. In addition, our material characterization using XRD and XPS did not show the presence of elemental N or GaN [50].…”
Section: The Growth Mechanism Of Ga2o3 Nanostructuresmentioning
confidence: 70%
“…The surface of the Ga 2 O 3 layer was observed by scanning electron microscopy (SEM) to confirm nanowire formations (FEI Nova NanoSEM430, FEI Company, Hillsboro, OR, USA) and to correlate it with electrical performances. Alhalaili et al [16] have observed, by SEM, energy dispersive X-ray spectroscopy (EDS), and high resolution transmission electron microscopy (HRTEM) equipped with EDS profile analysis, the formation of high-density, long, thin, and ultra-sharp Ga 2 O 3 nanowires obtained in the presence of the Ag catalyst at 1000 • C, which increased electron transfers [12,13]. After oxidation, electrical contacts were patterned at the top of the nanowires using a shadow mask, 5 nm Cr and 50 nm Au were sputtered using a Lesker sputtering system [9].…”
Section: Methodsmentioning
confidence: 99%
“…Alhalaili et al [16] have shown that both the nucleation and growth morphology of Ga 2 O 3 nanostructure film obtained by thermal oxidation depend on several factors, such as the substrate on which Ga 2 O 3 is grown, the use of Ag catalyst, and the oxidation temperature. The morphological and elemental analyses of Ga 2 O 3 nanostructures indicated an increase in the density that the Ga 2 O 3 nanowires obtained in the presence of the Ag catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation